PRESIDENT'S SOCIAL FORESTRY IN IMPROVING COMMUNITY WELFARE - Imelda Sapitri; M. Alpi Syahrin (NOMOI Law Review, 2021)
Indeed, Indonesia is a country that adheres to the notion of a "welfare state" with a "participatory welfare state" model which in social work literature is known as welfare pluralism.This model emphasizes that the state must continue to take part in handling social problems and the implementation of social security,although in its operation it still involves the community.The main goal of social forestry is the welfare or prosperity of the people.Locally, social forestry in Riau Province has an Indicative Map of Social Forestry Allocation (PIAPS) of 1.2 million hectares.However, the realization of social forestry achievements in Riau is far from the number of PIAPS.This achievement covers an area of 121,464.36 hectares with a total of 77 decrees and 24,136 households.Barriers to social forestry other than landconflicts, Social Forestry and Environmental Partnerships (PSKL), Working Groups (POKJA), the Environment and Forestry Service (DLHK) and the Forest Management Unit (KPH) have different ideas in accelerating social forestry.If the achievement of social forrestry is realized in accordance with the number of PIAPS 1.2 million hectares, it can help the community's economy so that the realization of community welfare in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia.